Proposed Social-Media Marketing Strategy to Improve Customer Engagement on Instagram (Case Study: The Hidden Heaven) - Nur, Muhammad Ikhsan; Garnida , Nita (Journal Research of Social Science, Economics, and Management, 2025)
The growing consumer demand for specialty coffee and the rise of home-brewing culture in Indonesia have created new market opportunities for coffee roasteries in the B2C market. However, The Hidden Heaven, a roastery based in Surakarta, remains highly dependent on B2B clients, exposing the business to sales instability. To seize these emerging opportunities, The Hidden Heaven needs to strengthen its efforts in the B2C market to attract and retain individual consumers. Specifically, this research addresses a strategic gap in the company’s use of Instagram for customer engagement. The objective is to develop a targeted social media marketing strategy that enhances customer engagement. Using a mixed-method approach, the study combines qualitative interviews with the company’s management and quantitative survey data from 354 Instagram-active consumers aged 18–35. Data were analyzed using SEM-PLS to test the effects of social media influencers (SMI), user-generated content (UGC), and carousel post formats on customer engagement. The results show that only content in the carousel post format has a significant impact. This study contributes to digital marketing practices by developing an evidence-based Instagram strategy tailored for the specialty coffee industry.